Micro-mechanics of CNT-engineered layered composites - Toh, William. (2011)
There has been increasing attention to utilizing carbon Nanotubes (CNTs) as nano-fillers in composite materials, such as Carbon Fiber Reinforced Plastics. However, the understanding of how randomly oriented CNTs affect mechanical properties of such composites is limited. This project serves to develop a model for determining the elastic properties of CNT-engineered composite materials using a mechanics of materials approach. Analysis of the properties was built progressively from the nano level, to the micro level and finally to the macro level. The process of making the model largely relied on first principle. The nano-level analysis divides the randomly distributed CNT-resin nano-composite into elemental cubes, each with CNT aligned in a different specific direction. Properties of each cube were calculated using equations derived in the course of this project, and then the cubes combined to simulate a random distribution of CNT within the CNT-resin nano-composite. The micro-level analysis involves calculation of properties of CFRP-CNT lamina. Each lamina is divided into elemental layers with equal width, but differs in the volume fractions of CNT and carbon fibers. The properties of the entire lamina were determined by combining all elemental layers. The macro-level analysis combines several laminae together to form the entire laminate composite. In the curing process, CNT distribution varies across the laminate thickness due to pressure differences. Therefore the laminae would have different properties. MATLAB programming platform was used to facilitate simulation of the modeling process. Typical simulation cases of the CNT-engineered materials are presented in comparison with published experimental and other data, where appropriate.